Esophageal atresia with tracheoesophageal fistula: A rare variant and cautionary tale - Nicole A. Wilson; Walter Pegoli, Jr; Christopher A. Gitzelmann; Theresa Foito; John J. Faria; Derek Wakeman (Elsevier, 2017)
Esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) are relatively common congenital anomalies. Additional variants of these anomalies have been reported, including EA-TEF associated with congenital esophageal stenosis (CES) and a few reports of EA-TEF associated with an esophageal web or membranous diaphragm. We report an extremely rare case of EA with distal TEF associated with both a CES and a separate esophageal web distal to the TEF. EA-TEF with an associated CES and/or mucosal web distal to the TEF presents both a diagnostic and management challenge, as the standard diagnostic/pre-operative work-up may not identify the distal areas of esophageal occlusion. Surgeons should be aware and should maintain a high index of suspicion for these anatomic variants as they can lead to operative complications. Use of a tube to confirm patency of the distal esophageal pouch as a standard technique during EA-TEF repair may help avoid the potential pitfalls associated with failure to recognize these conditions. Keywords: Congenital esophageal stenosis, Esophageal atresia, Esophageal web, Tracheoesophageal fistula